Customer's Purchase Decision in Alfamaret Tataaran II Minahasa - Manongko, Allen A. CH.; Indawati, Ninik; Oroh, Silvana S.A; Kaparang, Maria Melva (AIBPM Publisher, 2021)
This study aims to determine the partial effect of service quality and price perceptions on customer buying decisions; and the simultaneous influence of service quality and price perception on customer buying decisions at Alfamart Tataaran II Minahasa. This research applied a quantitative approach with a survey method. The population comprised consumers who have made purchases at Alfamart Tataaran II Minahasa. The research sample consisted of 150 respondents selected by accidental sampling. The data were collected through questionnaires and analyzed by multiple regression. The findings reveal a significant effect of service quality on customer buying decisions, a positive and significant influence on price perceptions on customer buying decisions, and a collective positive influence and significant service quality and price perceptions on customer decisions.